Design of polyzinc finger peptides with structured linkers - Moore, Michael (The National Academy of Sciences, 2001)
Zinc finger domains are perhaps the most versatile of all known DNA binding domains. By fusing up to six zinc finger modules, which normally recognize up to 18 bp of DNA, designer transcription factors can be produced to target unique sequences within large genomes. However, not all continuous DNA sequences make good zinc finger binding sites. To avoid having to target unfavorable DNA sequences, we designed multizinc finger peptides with linkers capable of spanning long stretches of nonbound DNA. Two three-finger domains were fused by using either transcription factor IIIA for the Xenopus 5S RNA gene (TFIIIA) finger 4 or a non-sequence-specific zinc finger as a “structured” linker. Our gel-shift results demonstrate that these peptides are able to bind with picomolar affinities to target sequences containing 0–10 bp of nonbound DNA. Furthermore, these peptides display greater sequence selectivity and bind with higher affinity than similar six-finger peptides containing long, flexible linkers. These peptides are likely to be of use in understanding the behavior of polydactyl proteins in nature and in the targeting of human, animal, or plant genomes for numerous applications. We also suggest that in certain polydactyl peptides an individual finger can “flip” out of the major groove to allow its neighbors to bind shorter, nontarget DNA sequences.